CITOTOXICIDADE E ESTRESSE OXIDATIVO CAUSADO POR NANOCÁPSULAS CONTENDO MELOXICAM EM CULTURA DE ESPLENÓCITOS DE CAMUNDONGOS BALB/C - Nascimento, Kátia (2013)
The toxicological sciences cover several areas including the toxicology, which studies the toxicity of nanoparticles (NPs) for use in the biological contact. NPs depending on how they interact with the cells can generate a series of imbalances, may be both cell membrane or in genetic material. This study evaluated the cytotoxicity and oxidative stress of nanocapsules (NCs) of meloxicam in cultured splenocytes of mice in vitro. We used mice of Balb/ c spleens were removed for the experiments. Cytotoxicity assays were performed as the 3 - (4,5) dimetiltialzolil -2,5 diphenyltetrazolium (MTT) and PicoGreen®, and also oxidative stress through the levels of thiobarbituric acid reactive species (TBARS), catalase activity and the levels of non-protein thiols (NPSH). The results showed that both NCs meloxicam (MN) NCs white (NB) and free meloxicam (ML) were cytotoxic to splenocytes. MF increased lipid peroxidation, but did not change antioxidant defenses, while MN did not alter the oxidative stress parameters. The NC constituents were isolated and it was performed cytotoxicity assays in splenocytes of mice. We demonstrated that all components (PCL, Tween 80, Span 60 and oil - medium chain triglyceride) caused cytotoxicity and only the PCL and Tween 80 caused damage to the nuclear membrane. Therefore, we can conclude that NC, NB and MF caused cytotoxicity, but only NB and MF produced oxidative stress. Moreover, cytotoxic effects of NCs constituents isolated did not intense. In this context, this study revealed that the NC components act synergistically to cause toxicity.